Strategi Perancangan Dalam Meningkatkan Vitalitas Kawasan Perdagangan Johar Semarang - Susiyanti, Farma Aria (Center for Research and Community Services ITB, 2003)
Many old commercial areas in Indonesian cities face unbalance vitality and unclear spatial planning. Being ignored and degraded, the old commercial districts become less attractive to other (new) commercial districts. A design strategy is needed to restore the vitality and image of old commercial districts. The goal of this research is to formulate design strategy to improve the vitality of the area so that a secure, convenient, attractive and amenity can be achieved. The formulation is done by formulating the norms of revitalization design strategy approach based on assessment of vitality criteria, design criteria and the influential factors of vitality problems. This research takes Johar Commercial Area in Semarang City for study case that Semarang’s People were very proud of it. Description and assessment level of vitality is viewed from activity aspect, by dividing the area of research into 4 sub areas (Johar, Kanjengan, Yaik and Johar Shopping Center) to alleviate assessment process. From that analysis, there are unbalance level of vitality problems. The influence factor of those vitality problems are emphasized on design aspect. Design strategy of area revitalization is obtained by doing SWOT analysis based on strength, weakness, opportunity, and threat area. Strategies are divided into general and special strategy with concerns of the unity of each sub area.Keywords: design strategy, commercial districts, vitality, revitalization